Unmute: an Android app for Deaf and Hard Hearing Students - Vadhavkar, Aditya; Sengupta, Abhishek; Jadhav, Rahul; Patil, Rishabh; Patil, Vaishnavi (International Journal of Computer Sciences and Engineering, 2025)
Hearing deficit individuals face challenges that cannot be avoided but they can overcome it with the powerful tool of education. It is a tool that is undeterred to the barriers of communication and thus it promises them a normal life of equality and independence. This paper is an attempt to propose the android application with modules for students, volunteers and donors catering to various aspects of learning to become a one stop solution for the hearing impaired. The underlined features of the application are text-to-speech conversion, a pool of tests with detailed progress report for students were the study resources are monitored by volunteer module. Additionally donation module records donors donating phones, books and money.